Goal-Side Selection in Soccer Penalty Kicking When Viewing Natural Scenes - Weigelt, Matthias; Memmert, Daniel (Frontiers in Psychology, 2012)
The present study investigates the influence of goalkeeper displacement on goal-side selection in soccer penalty kicking. Facing a penalty situation, participants viewed photo-realistic images of a goalkeeper and a soccer goal. In the action selection task, they were asked to kick to the greater goal side, and in the perception task, they indicated the position of the goalkeeper on the goal line. To this end, the goalkeeper was depicted in a regular goalkeeping posture, standing either in the exact middle of the goal or being displaced at different distances to the left or right of the goal’s center. Results showed that the goalkeeper’s position on the goal line systematically affected goal-side selection, even when participants were not mindful of the displacement. These findings provide further support for the notion that the implicit processing of the stimulus layout in natural scenes can effect action selection in complex environments, such in soccer penalty shooting.